Learning Innovations in Enhancing Teachers' Emotional and Spiritual Skills - Rahman, Yurni (Journal La Edusci, 2025)
Learning innovations relating to emotional and spiritual intelligence based on this study are how the innovations contribute to the advancement of the teachers professional capacity of the elementary schools in Gorontalo Regency, Indonesia. The research understands that not just the knowledge of the material is sufficient to become a good teacher and looks into the pedagogical activities that would be involved in emotional regulation, moral presence, and spiritual clarity. A qualitative case study method was used to collect the data by means of interviews, classroom observations, and document analysis among five elementary schools that participated in the associated training program actively. The results indicate that teachers who develop emotional and spiritual skills show an improvement of self-regulation, strengthening relationship to their students and self-rediscovery of ethical commitment in their professions. Nevertheless, the combination of such competencies may be hampered by structural impediments, such as time requirements, diminished institutional assistance, and the prevalence of academically minimizing structures of policy-making. The research suggests a shift in teacher growth and school culture that claims emotional and spiritual intelligence as an essential part of life, rather than optional extras. The personal experiences of the teachers brought into the foreground with the support of this research will be integrated into the greater literature concerning wholistic education, character development, and the buzzs so-called ethical reconstruction of instruction.